Cm-E-supermagic labeling of graphs. Issue 1 (2nd January 2020) - Chithra, C.; Marimuthu, G.; Kumar, G.
Abstract: A simple graph G admits an H -covering if every edge in E ( G ) belongs to a subgraph of G isomorphic to H . The graph G is said to be H -magic if there exists a total labeling f : V ( G ) ∪ E ( G ) → { 1, 2, 3, …, | V ( G ) | + | E ( G ) | } such that for every subgraph H ′ of G isomorphic to H, ∑ v ∈ V ( H ′ ) f ( v ) + ∑ e ∈ E ( H ′ ) f ( e ) is constant. Additionally, the labeling f is called H - E supermagic labeling if f ( E ( G ) ) = { 1, 2, 3, …, | E ( G ) | } . In this paper, we study C m - E -supermagic labeling of some families of connected graphs.